Early and delayed cholecystectomy in acute cholecystitis - Kargici, H.; Yildirim, A.M.; Akkus, M.A. (My University, 1992)
[Abstract Not Available]
Keywords: article; cholecystectomy; cholecystitis; human; major clinical study; postoperative complication; surgical approach